Heterozygosity and Fixation Index for ABO Gene in Barak Valley Populations vis-a-vis a Few Exotic Populations - Supriyo CHAKRABORTY (Notulae Scientia Biologicae, 2011)
In a genetic study of 26 human populations including 2 major endogamous populations (Hindus and Muslims) of Barak Valley in Assam and 24 exotic populations, observed heterozygosity (Ho), fixation index (F) and Panmictic index (P) for ABO gene were estimated from gene frequency data to reveal the extent of inbreeding that has taken place in each population during evolution. Observed heterozygosity, a measure of genetic variation, ranged from 0.3254 to 0.6086 in these populations. Expected Hardy-Weinberg heterozygosity of ABO gene was estimated as 0.6666 assuming the occurrence of all the three alleles in equal frequency. Fixation index was the highest in the population of Sudan (51.18%) followed by Australia (48.51%) and Iceland (38.28%) indicating the occurrence of high inbreeding and the presence of more homozygosity in these populations during evolution. But the fixation index was the lowest in the population of South China (8.70%) followed by Central Asia (11.82%) and Russia (12.96%). It suggested the occurrence of low inbreeding and hence more outbreeding in these populations resulting in the existence of more heterozygosity (high genetic variation) in these populations. Panmictic index, a measure of outbreeding, is the opposite of fixation index and it varied from 48.82 (Sudan) to 91.30% (South China). The population showing the highest fixation index recorded the lowest panmictic index and vice-versa. In evolutionary context, outbreeding in human populations would be more desirable to reduce the incidence of genetic diseases caused by recessive genes and to enhance heterozygosity for those loci for better adaptation of future generations, possibly at the cost of gradually increasing genetic load in the population.